(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
The scientific world has recently become more interested in fasting as a possible therapeutic approach for cancer. Fasting and fasting-mimicking diets (FMDs) have shown great potential in controlling cancer progression, treating various cancers, and improving the outcomes of patients receiving anticancer therapy. The review of multiple studies conducted on several trials in this study indicates that fasting might make cancer cells vulnerable, protect normal cells from chemotherapy, and decrease growth signals associated with cancer such as IGF-1. Ongoing research provides hope that fasting protocols can safely be incorporated into a physician guided cancer treatment protocol, although additional human trials are warranted.